2015
DOI: 10.1590/0074-02760140243
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive endophytic fungi isolated from Caesalpinia echinata Lam. (Brazilwood) and identification of beauvericin as a trypanocidal metabolite from Fusarium sp.

Abstract: Aiming to identify new sources of bioactive secondary metabolites, we isolated 82 endophytic fungi from stems and barks of the native Brazilian tree Caesalpinia echinata Lam. (Fabaceae). We tested their ethyl acetate extracts in several in vitro assays. The organic extracts from three isolates showed antibacterial activity against Staphylococcus aureus and Escherichia coli [minimal inhibitory concentration (MIC) 32-64 μg/mL]. One isolate inhibited the growth of Salmonella typhimurium (MIC 64 μg/mL) and two iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 40 publications
2
24
0
1
Order By: Relevance
“…Our study also highlighted the relationship between phenolic and flavonoid content to the antioxidant nature of the natural products. Our study is in agreement with the studies reported earlier about the positive correlation between the phenolic content and the antioxidant potential of natural products (Ben et al 2009; Yadav et al 2014; Campos et al 2015). …”
Section: Discussionsupporting
confidence: 94%
“…Our study also highlighted the relationship between phenolic and flavonoid content to the antioxidant nature of the natural products. Our study is in agreement with the studies reported earlier about the positive correlation between the phenolic content and the antioxidant potential of natural products (Ben et al 2009; Yadav et al 2014; Campos et al 2015). …”
Section: Discussionsupporting
confidence: 94%
“…Fungi of the genus Xylaria are often isolated as endophytic from tropical plants and their metabolites have antibacterial activity, as observed in prospecting studies (Souza et al, 2004;Campos et al, 2015).…”
Section: Discussionmentioning
confidence: 96%
“…Asterosporium and Aureobasidium were isolated only at 18°C, while Guignardia, Aspergillus, Botrytis, and Didymostilbe only at 28°C. Studies on endophytic fungi generally use temperatures between 25 and 28°C (Premalatha and Kalra, 2013;Campos et al, 2015;Ferreira et al, 2015).…”
Section: Isolation and Identification Of Endophytic Fungimentioning
confidence: 99%